Becoming a Good BookTuber - Suárez, Mᵃ del Mar; González Argüello, M. Vicenta (RELC journal, 2020)
Audiovisual platforms like YouTube facilitate the introduction of informal learning practices for their pedagogical exploitation both in class and online. One such practice is the creation of a BookTuber community for recommending books, thus making it possible for students to engage in an out-of-class community where common interests can be shared. In this innovations in practice article, we present a project carried out with two English for Specific Purposes (ESP) groups of Media Studies of the University of Barcelona. The aim of this project was to determine features that make a BookTuber a good communicator so students could apply these features to their own BookTube video practice. Students could then use these features as a guideline for peer-review comments published on YouTube and the creation of an online BookTuber community. Students were first introduced to the concept of intertextuality in order to understand how it fosters connections among audiovisual consumers. The BookTuber community was then presented and the students viewed and analysed several BookTube videos with the objective of creating an evaluation rubric identifying the key aspects of a good BookTuber. The students then created their own BookTube video and uploaded it onto YouTube. They were also required to watch at least two videos created by their peers, post comments that considered key aspects included in the evaluation rubric and express their personal reactions to and opinions of the videos. In addition, an extended version of the peer-review was also required to achieve subject credits. This twofold feedback allowed for the practice of two discourse styles for the same content: informal (for YouTube) and formal (for the teacher). As a result, students had firsthand experience of becoming a BookTuber while developing their critical thinking skills for peer evaluation and academic and professional purposes of career development.